Relations on Ensuring the Rights and Freedoms of a Man and Citizen as a Component of the Subject Matter of Administrative Law - A. T. Komziuk; Ye. A. Lypii (Bulletin of Kharkiv National University of Internal Affairs)
The relations arising in the activity of public administration concerning the provision of human rights and freedoms, which are recognized as a priority component of the subject matter of administrative regulation, are characterized.  It is emphasized that one of the main, conceptual, most important and at the same time the most controversial issues is still the understanding of the subject matter and system of administrative law.